PENGEMBANGAN ENSIKLOPEDIA DIGITAL BERBASIS KEARIFAN LOKAL TERINTEGRASI PROFIL PELAJAR PANCASILA MATERI KERAGAMAN BUDAYA KELAS IV DI SEKOLAH DASAR - Sobiyatul Mutamima; Riawan Yudi Purwoko; Suyoto (LPPM Universitas Cipta Mandiri, 2024)
This research was motivated by problems that occurred due to a lack of teaching materials, digital teaching materials based on local wisdom had never been implemented, and teachers' lack of time and energy in developing teaching materials. This research aims to determine the development procedures, validity, practicality and effectiveness of a digital encyclopedia product based on local wisdom integrated with Pancasila student profiles on class IV cultural diversity. This research method uses the 4D model R&D (Research and Development) method (Define, Design, Develop, Disseminate). Data collection techniques use observation, interviews, questionnaires, tests and documentation methods. From the results of research data processing, the results of the 4D development procedure were obtained, product validity with an average of 95.8% (very valid), product practicality obtained an average of 92.6% (very practical), product effectiveness was obtained from completeness which obtained an average -average 97.8% (very effective). The results of the effectiveness data are supported by the gain score with an average result of 0.794 (high) and the results of the implementation of student learning and activities with an average of 93.8% (very good). It can be concluded that the digital encyclopedia based on local wisdom integrated with Pancasila student profiles on cultural diversity material can be used as teaching material for class IV elementary schools because it meets the criteria of being valid, practical and effective.